Grey's Hospital, Pietermaritzburg 1855 - 1985 - Jennifer G Duckworth (AOSIS, 1985)
The first matron of Grey's Hospital, Mrs Isabella O 'Hara, was appointed in October 1855 and she presided over a temporary hospital which was established in a house until such time as the hospital building should be ready. The patients were mainly lunatics and destitute people who had until then been accommodated in a room at the goal. The sick were usually cared for in their homes.